1994
DOI: 10.1063/1.166028
|View full text |Cite
|
Sign up to set email alerts
|

Chemical turbulence and standing waves in a surface reaction model: The influence of global coupling and wave instabilities

Abstract: Among heterogeneously catalyzed chemical reactions, the CO oxidation on the Pt(110) surface under vacuum conditions offers probably the greatest wealth of spontaneous formation of spatial patterns. Spirals, fronts, and solitary pulses were detected at low surface temperatures (T<500 K), in line with the standard phenomenology of bistable, excitable, and oscillatory reaction-diffusion systems. At high temperatures (T greater, similar 540 K), more surprising features like chemical turbulence and standing waves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 39 publications
(2 reference statements)
3
42
2
2
Order By: Relevance
“…As a result, the defect number fluctuates in time according to a Poisson distribution and the variance of the defect number was predicted to be equal to its temporal mean [341]. Studies of the defect-statistics in the Bär-Eiswirth model [342,343] revealed that spiral breakup leads to an initial fast transient increase of the defect number, but shows substantial deviations from the prediction of the model by Gil et al In particular, the variance close to the breakup instability is much smaller than the mean, which is due to a strong anticorrelation between topological defects reminiscent of the spatial correlation of particles in a liquid. Further away from the breakup instability spatial correlations are much weaker and the defect statistics are in line with the prediction of the simple theory by Gil et al [341].…”
Section: Characterization Of Electrical Turbulencementioning
confidence: 99%
“…As a result, the defect number fluctuates in time according to a Poisson distribution and the variance of the defect number was predicted to be equal to its temporal mean [341]. Studies of the defect-statistics in the Bär-Eiswirth model [342,343] revealed that spiral breakup leads to an initial fast transient increase of the defect number, but shows substantial deviations from the prediction of the model by Gil et al In particular, the variance close to the breakup instability is much smaller than the mean, which is due to a strong anticorrelation between topological defects reminiscent of the spatial correlation of particles in a liquid. Further away from the breakup instability spatial correlations are much weaker and the defect statistics are in line with the prediction of the simple theory by Gil et al [341].…”
Section: Characterization Of Electrical Turbulencementioning
confidence: 99%
“…It should be noted that the inhomogeneous oscillating states and standing waves have been previously discussed for CO oxidation on Pt(110) where the main mechanism responsible for these phenomena is the coupling through the gas phase [10,11,12]. In contrast to Pt(110), on Pt(100) the inhomogeneities in the surface geometry play a central role.…”
Section: Consequence Of Surface Inhomogeneities: Chemical Turbulencementioning
confidence: 93%
“…Also the 1D version of the model suggested for describing a surface reaction (CO oxidation on Pt(110)) [39] is promising, because the qualitative change of the pattern with the size of the system might be observed experimentally, provided that the experimental setup was as close to 1D as possible. It is worth noting that our model is also realistic and could be realized in experiments in a 1D CFUR with two enzymatic reactions.…”
Section: Discussionmentioning
confidence: 99%